2012
DOI: 10.1186/1472-6920-12-67
|View full text |Cite
|
Sign up to set email alerts
|

How do postgraduate GP trainees regulate their learning and what helps and hinders them? A qualitative study

Abstract: BackgroundSelf-regulation is essential for professional development. It involves monitoring of performance, identifying domains for improvement, undertaking learning activities, applying newly learned knowledge and skills and self-assessing performance. Since self-assessment alone is ineffective in identifying weaknesses, learners should seek external feedback too. Externally regulated educational interventions, like reflection, learning portfolios, assessments and progress meetings, are increasingly used to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 59 publications
2
74
0
1
Order By: Relevance
“…In the previous study, we interviewed GP trainees on their self-regulated learning (Sagasser et al 2012). That study revealed a short and long loop of self-regulated learning.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the previous study, we interviewed GP trainees on their self-regulated learning (Sagasser et al 2012). That study revealed a short and long loop of self-regulated learning.…”
Section: Discussionmentioning
confidence: 97%
“…The literature reveals that informed self-assessment, facilitated reflection and directed self-guided learning can support SRL (Brydges and Butler 2012;Brydges et al 2010;Butler and Brydges 2013;Sargeant et al 2008;Schumacher et al 2013). Also, in postgraduate training supervisors can have a supportive role (Boendermaker et al 2000;Brydges et al 2010;Kilminster et al 2007;Mann et al 2001;Sagasser et al 2012;Sandars and Cleary 2011;Sutkin et al 2008;Wearne et al 2012). Supervisors, who are experienced clinicians and trained in their supervisory tasks, can help identify trainee skill levels and set an appropriate level of challenge, occasionally in ways trainees would not attempt themselves.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Schön, there is a difference between 'reflectionin-action' and 'reflection-on-action' (Schön 1987). Sagasser et al (2012) found that learning in practice occurred in a short and a long loop, both involving self-monitoring. Their analysis revealed that trainees reflected during and after activities, which suggests that their self-monitoring may reflect Schön's 'reflection-in-action' (short loop) and 'reflection-on-action' (long loop).…”
Section: Practice Pointsmentioning
confidence: 99%
“…La implicación de los estudiantes en su propia evaluación les permite llevar a cabo procesos de autoreflexión (Hudson, Rienits, Corrin y Olmos, 2012;Chaffey, de Leeuw y Finnigan, 2012;O'Sullivan et al, 2012;Van Schaik, Plant y O`Sullivan, 2013) que conllevan mecanismos de retroalimentación en su aprendizaje (Nicol y Macfarlane-Dick, 2006;Sagasser, Kramer y Van Der Vleuten, 2012;Dannefer y Prayson, 2013;Garner, Gusberg y Kim, 2014).…”
Section: Importancia Del Portafolios Para La Evaluación De Competenciasunclassified